Peningkatan Collaboration Skill dan Hasil Belajar Melalui Pembelajaran Berdiferensiasi Kelas IV SD - Aly, Lathifa (Jurnal Pendidikan Guru Profesional, 2025)
The aim of this research is to improve collaboration skills and learning outcomes through differentiated learning on plant body material and function of class IV SDN Ambulu 01. The research design used is class action research. The subject of this study are students class IV C SDN Ambulu 01 consisting of 23 students. Data collection using interviews, observations, tests and documentation. The minimum grade gradient for collaboration skills is 65, while learning outcomes are 75. The results of the study showed that students of class IV C SDN Ambulu 01 achieved better collaboration skills and learning outcomes when applying differentiated learning. This is seen from the classical access of collaboration skills of Cycle I of 56%, then increased in Cycle II of 73%. The same is the classical access of learning outcomes of cycle I by 56%, and then increases in cycle II by 76%. So it can be concluded that the application of differentiated learning can improve the collaboration skill and learning outcome of students of class IV SDN Ambulu 01.